Performance and risk assessment framework for sustainable networks - Almeida, António (2011)
Nowadays, supply chains and specially Collaborative Networks are increasingly aware of sustainability issues and continuously seek to meet current human needs while preserving the environment so that these needs can be met not only in the present, but for future generations. In order to achieve this goal, particularly within Collaborative Networks, present decision making related with sustainability policies and practices, becomes a critical issue for the future of each stakeholder in the network. Sustainability networks must ensure that economic, environmental and social axes are fully aligned within each partner. To accomplish this, "performance metrics" for the entire network are required not only concerning the economic value of a business, but also in its environmental and social impacts. In line with this concept, organizations need to improve the quality of performance assessment namely in the sustainability areas. This paper focuses on this topic, presenting a new approach for performance and risk assessment within sustainable networks.